THE RELATIONSHIP BETWEEN POST PARTUM DEPRESSION WITH MOTHER-BABY EMOTIONAL BONDING, BREASTFEEDING ABILITY, MARRIAGE SITUATION RELATIONSHIP IN PUSKESMAS MALANG REGION - Putri Ragil Kusumawardani; Sri Poeranto; Asti Melani Astari (Journal of Nursing Science Update (JNSU), 2017)
A woman's transition into motherhood brings about physical and psychological changes. The changes require adjustments to her daily roles and activities. If the postpartum mother is not able to adapt well, then there will be a mood disorder. Depression is a part of mood disorder. The impact of postpartum depression will disrupt the mother-infant bonding, breastfeeding self-efficacy and the changing of marriage partnership. The purpose of this research was to analyze the impacts most affected by the incidence of postpartum depression in the working area of public health Malang City. The research used descriptive correlational method with cross sectional, with purposive sampling of 70 respondents in the period April 26th, 2017 - May 30th, 2017. The results are 93% of post-partum mothers experience moderate depression affecting low breast-feeding ability 54.3%, poor marital relationship situation 52.9% and moderate emotional bonding disturbances 47.1%. The result of bivariate analysis is known to the effect of postpartum depression, namely breastfeeding ability (p value = 0,011), marital relationship situation (p value = 0.014), emotional bond (p value = 0,021). The results of logistic regression test showed that the impact most influenced by postpartum depression was the ability of breastfeeding (p value = 0,011; ExpB 6,394). Postpartum mothers can predict the incidence of depression by looking at three aspects directly including the breastfeeding self-efficacy, marriage partnership and mother-infant bonding. Of the three aspects of the most influential is the breastfeeding self-efficacy. In the next research should be done at a wider population level in order to be able to cover the area of Malang generally.